Survival with Newly Diagnosed Metastatic Prostate Cancer in the “Docetaxel Era”: Data from 917 Patients in the Control Arm of the STAMPEDE Trial (MRC PR08, CRUK/06/019) - James, Nicholas David; Spears, Melissa R.; Clarke, Noel W.; Dearnaley, David P.; De Bono, Johann S.; Gale, Joanna; Hetherington, John; Hoskin, Peter J.; Jones, Robert J.; Laing, Robert; Lester, Jason F.; McLaren, Duncan; et al. (European urology, 2015)
Prostate cancer (PCa) is the second most common disease among men worldwide. It is important to know survival outcomes and prognostic factors for this disease. Recruitment for the largest therapeutic randomised controlled trial in PCa—the Systemic Therapy in Advancing or Metastatic Prostate Cancer: Evaluation of Drug Efficacy: A Multi-Stage Multi-Arm Randomised Controlled Trial (STAMPEDE)—includes men with newly diagnosed metastatic PCa who are commencing long-term androgen deprivation therapy (ADT); the control arm provides valuable data for a prospective cohort. Describe survival outcomes, along with current treatment standards and factors associated with prognosis, to inform future trial design in this patient group. STAMPEDE trial control arm comprising men newly diagnosed with M1 disease who were recruited between October 2005 and January 2014. Overall survival (OS) and failure-free survival (FFS) were reported by primary disease characteristics using Kaplan-Meier methods. Hazard ratios and 95% confidence intervals (CIs) were derived from multivariate Cox models. A cohort of 917 men with newly diagnosed M1 disease was recruited to the control arm in the specified interval. Median follow-up was 20 mo. Median age at randomisation was 66 yr (interquartile range [IQR]: 61–71), and median prostate-specific antigen level was 112 ng/ml (IQR: 34–373). Most men (n=574; 62%) had bone-only metastases, whereas 237 (26%) had both bone and soft tissue metastases; soft tissue metastasis was found mainly in distant lymph nodes. There were 238 deaths, 202 (85%) from PCa. Median FFS was 11 mo; 2-yr FFS was 29% (95% CI, 25–33). Median OS was 42 mo; 2-yr OS was 72% (95% CI, 68–76). Survival time was influenced by performance status, age, Gleason score, and metastases distribution. Median survival after FFS event was 22 mo. Trial eligibility criteria meant men were younger and fitter than general PCa population. Survival remains disappointing in men presenting with M1 disease who are started on only long-term ADT, despite active treatments being available at first failure of ADT. Importantly, men with M1 disease now spend the majority of their remaining life in a state of castration-resistant relapse. Results from this control arm cohort found survival is relatively short and highly influenced by patient age, fitness, and where prostate cancer has spread in the body. Data from the control arm of the STAMPEDE trial show that survival remains poor, particularly for younger men with bony metastatic prostate cancer. Men spend substantial time in a castration-resistant relapse state. New approaches are urgently needed. These data will help plan new randomised comparisons in this setting.